Building a Disaster-Resilient Community in Taiwan: A Social Capital Analysis of the Meizhou Experience - Yang, Alan Hao (2020)
Resilience has always been key to successful disaster governance throughout the world. Local communities can play an important role in promoting disaster preparedness and executing front-line relief to strengthen the effectiveness and efficiency of both local and national disaster governance. This article addresses a unique case of how a flood-prone, rural, and ageing community in Yilan County, Taiwan, successfully mobilized its citizens for disaster preparedness. Through the lens of social capital analysis, this article unpacks how Bonding Social Capital, Bridging Social Capital, and Linking Social Capital work, by tracing the process through which awareness of disaster resilience was developed and practised in the Meizhou Community. Since 2012, Meizhou has been recognized as a model of disaster preparedness and relief in Taiwan, and in 2019 this recognition was extended to the wider Indo-Pacific region. We begin the discussion of this article by contextualizing social capital as a theoretical departure to the empirical analysis of the Meizhou experience. This is followed by an exploration of how Bonding Social Capital was able to consolidate the community, and how Bridging Social Capital can facilitate the collaboration among functional groups in and beyond the Meizhou locality, and to what extent Linking Social Capital can implement Meizhou’s experience on a national and even international scale. This article is based on a qualitative assessment of long-term fieldwork, interviews, and participatory observation conducted by the authors in the Meizhou community.